2021
DOI: 10.1177/01945998211053197
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Children’s Preoperative Fear with an Educational Pop‐up Book: A Randomized Controlled Trial

Abstract: Objective Preoperative education empowers children to approach surgery with positive expectations, and providers need efficient, child-focused resources. This study aimed to evaluate an interactive pop-up book as a tool for explaining surgery, managing preoperative anxiety, and strengthening coping strategies. Study Design Prospective randomized controlled trial. Setting Pediatric outpatient surgery center. Methods Patients ages 5 to 12 undergoing outpatient surgery read a pop-up book about anesthesia (interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
8
0
1
Order By: Relevance
“…This finding is in line with the results of previous research. Cordray et al (2022) found that reading children an educational book reduced their fear before surgery. Binay Yaz and Bal Yilmaz (2022) showed that an educational animation film was an effective method for reducing fear before surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with the results of previous research. Cordray et al (2022) found that reading children an educational book reduced their fear before surgery. Binay Yaz and Bal Yilmaz (2022) showed that an educational animation film was an effective method for reducing fear before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…in the preoperative period are helpful in reducing children's fear, pain and anxiety (Aytekin et al, 2016; Chow et al, 2016; Forouzandeh et al, 2020; Mohamed & Elattar, 2019; Taha & El‐Sayed, 2021). Reading stories, which is one of these methods, is helpful in reducing children's fear and anxiety (Aydın & Uyar, 2021; Bülbül & Arıkan, 2018; Cordray et al, 2022; Durgut, 2021). When the literature is examined, no study has been found about the effect of reading a preoperative preparation‐themed storybook to the child by the mothers on the preoperative fear and anxiety level of the children.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated an approach that integrated several previous relatively independent approaches to provide children with an active participatory [23][24][25][26], multimedia-based home-initiated educational intervention prior to admission. Since this experiment incorporates parents and includes three aspects of children's audio-visual stimulation, active painting, and reading, it is more effective than other experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Development of the “Ready for Tonsillectomy” mobile application began as an adaptation of an interactive book that our team previously piloted 21 . The pop‐up book was designed to engage children in hands‐on education about their surgery without requiring expert guidance from a provider or child life specialist.…”
Section: Methodsmentioning
confidence: 99%